Analisis Moderasi dan Mediasi Dukungan Sosial Terhadap Pengaruh Empati Pada Keterlibatan Akademik Siswa Sekolah - Ratu Mas Zahra Nuraini Nawang Wulan; Naya Hasna Ainayya; Rika Agustina Ritonga; Suroya Lailata Hafilah (CV. Akademi Merdeka, 2025)
This study investigates the effect of empathy on elementary school students' academic engagement by examining the mediating and moderating roles of social support. Employing a quantitative survey design, the study involved 249 students from four elementary schools selected through stratified random sampling. Data were collected using questionnaires that assessed three primary constructs: empathy, social support, and student engagement. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The findings reveal that empathy significantly and positively influences both student engagement and perceived social support. However, social support does not have a direct significant impact on student engagement and fails to mediate the relationship between empathy and engagement. Interestingly, empathy was found to moderate the relationship between social support and engagement negatively, indicating that students with high levels of empathy tend to participate actively in learning regardless of external support. These results highlight the critical role of empathy in fostering student engagement and support the integration of social-emotional learning strategies in elementary education settings.